Mineralization of palm oil mill effluent by advanced oxidation processes: A review on current trends and the way forward - Vijayan, Veena; Joseph, Collin G.; Taufiq-Yap, Yun Hin; Gansau, Jualang Azlan; Nga, Janice L.H.; Li Puma, Gianluca; Chia, Poh Wai (Elsevier, 2024)
Palm oil mill effluent (POME) is regarded as deleterious to the environment, primarily owing to the substantial volume of waste it produces during palm oil extraction. In terms of contaminant composition, POME surpasses the pollutant content typically found in standard municipal sewage, therefore releasing it without treatment into water bodies would do irreparable damage to the environment. Main palm oil mills are normally located in the proximity of natural rivers in order to take advantage of the cheap and abundant water source. The same rivers are also used as a water source for many villages situated along the river banks. As such, it is imperative to degrade POME before its disposal into the water bodies for obvious reasons. The treatment methods used so far include the biological processes such as open ponding/land application, which consist of aerobic as well as anaerobic ponds, physicochemical treatment including membrane technology, adsorption and coagulation are successful for the mitigation of contaminants. As the above methods require large working area and it takes more time for contaminant degradation, and in consideration of the strict environmental policies as well as palm oil being the most sort of vegetable oil in several countries, numerous researchers have concentrated on the emerging technologies such as advanced oxidation processes (AOPs) to remediate POME. Methods such as the photocatalysis, Fenton process, sonocatalysis, sonophotocatalysis, ozonation have attained special importance for the degradation of POME because of their efficiency in complete mineralization of organic pollutants in situ. This review outlines the AOP technologies currently available for the mineralization of POME with importance given to sonophotocatalysis and ozonation as these treatment process removes the need to transfer the pollutant while possibly degrading the organic matter sufficiently to be used in other industry like fertilizer manufacturing.